Odpowiedzi

2009-12-23T12:59:19+01:00
((x+|x|)/2)² + ((x-|x|)/2)²=x²
(x+|x|)/4 + (x-|x|)/4=x² /*4
x²+2x|x|+|x|²+x²-2x|x|+|x|²=4x²
2x²+2|x|²=4x²
x² jest dodatni i |x|² jest dodatni, zatem x²=|x|² zatemL
4x²=4x² co należało udowodnić :) pozdrawiam.
Najlepsza Odpowiedź!
2009-12-23T14:46:28+01:00
((x+|x|)/2)² + ((x-|x|)/2)² = x²
_____________________________
(x+|x|)/4 + (x-|x|)/4 = x² /*4
____________________________
x²+2x|x|+|x|²+ x²-2x|x|+|x|² = 4x²
_____________________
2x²+2|x|²=4x²
_________________
x²=|x|²
_____________
4x²=4x²